Leukocyte ACHT : a link between the neuroendocrine and immune systems - Ferreira, Johan Andries (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.(Med.Sciences) -- University of Stellenbosch, 1992.